Metastrongyloid Infection with Aelurostrongylus abstrusus, Troglostrongylus brevior, Oslerus rostratus and Angiostrongylus chabaudi in Feral Cats from the Canary Islands (Spain) - Katherine García-Livia; Ricardo Reyes; Virginia Amaro-Ramos; Edgar Baz-González; Natalia Martin-Carrillo; Eligia Rodríguez-Ponce; Pilar Foronda (Animals, 2023)
Lungworms are a major cause of feline respiratory disease, frequently underdiagnosed due to its presentation of symptoms being similar to that of other feline respiratory pathologies. Epidemiological data about these nematodes are scarce in the Canary Islands (Spain). Given the veterinary importance of these parasites, the aim of the present study was to improve the current epidemiological knowledge of the lungworm species that could be affecting feral cats in this archipelago. A total of 29 feral cats from La Gomera were analyzed. The respiratory tract of each animal was inspected and the nematodes obtained were identified by morphological keys and molecular techniques. Metastrongylids were detected to be widely distributed throughout the island with a prevalence of 55.2% (16/29). The species Aelurostrongylus abstrusus, Troglostrongylus brevior, Oslerus rostratus and Angiostrongylus chabaudi were identified. Also, coinfections with A. chabaudi and O. rostratus were detected in two animals. The present study shows a high diversity of lungworms in feral cats in La Gomera, with the first report of A. chabaudi and T. brevior for the Canary Archipelago and the first citation of A. chabaudi in cats for Spain. The wide distribution and high prevalence found in this study indicate a high risk of exposure to pulmonary infections in cats.